Discussion of Determinants of the Justifiability of Performance in Ill- Structured Audit Tasks - Hackenbrack, Karl (Journal of Accounting Research, 1997)
Karl Hackenbrack, Discussion of Determinants of the Justifiability of Performance in Ill- Structured Audit Tasks, Journal of Accounting Research, Vol. 35, Studies on Experts and the Application of Expertise in Accounting, Auditing, and Tax (1997), pp. 125-130